ESD. - Voldman, Steven H. (ESD series., 2015)
This book is about analog circuit design layout and schematic development, architecture of chips, and ESD design. Two critical design aspects for analog and power integrated circuits are combined. A comprehensive list of practical application examples is used to demonstrate the combination of both techniques and any potential design trade-offs. Features: describes analog design fundamentals (circuit fundamentals) as well as outlining the various ESD implications; covers a large breadth of subjects and technologies, such as CMOS, LDMOS, BCD, SOI, and thick body SOI; establishes an "ESD analog design" discipline that distinguishes itself from the alternative ESD digital design focus; focuses on circuit and circuit design applications. --